(untitled) (Asian Business Research, 2022)
Warehousing as one of the main functions of logistics core functions, the optimization of warehousing operation process has been highly valued by the entire industry. Based on RFID technology, taking Jingdong Huizhou Huiyang Logistics Center as an example, combined with the analysis of the current situation of its warehousing operation process, the process design is optimized from the three aspects of warehousing, warehouse management and outbound storage, and the simulation modeling of the inbound and outbound processes is carried out by using Flexsim software. The results show that: 1) The warehousing operations of logistics centers have pain points of long waiting time in storage, low inventory efficiency and high cargo loss rate. 2) Through the comparative analysis of the modeling results before and after optimization, RFID technology can effectively improve the efficiency of the warehousing operation process, and determine the feasibility of the optimized process to improve the efficiency of the warehousing operation process.